Involvement of Inflammatory Cytokines in Antiarrhythmic Effects of Clofibrate in Ouabain-Induced Arrhythmia in Isolated Rat Atria - Somayeh Moradi; Vahid Nikoui; Muhammad Imran Khan; Shayan Amiri; Farahnaz Jazaeri; Azam Bakhtiarian (Hindawi Limited, 2016)
Considering the cardioprotective and anti-inflammatory properties of clofibrate, the aim of the present experiment was to investigate the involvement of local and systemic inflammatory cytokines in possible antiarrhythmic effects of clofibrate in ouabain-induced arrhythmia in rats. Rats were orally treated with clofibrate (300 mg/kg), and ouabain (0.56 mg/kg) was administered to animals intraperitoneally. After induction of anesthesia, the atria were isolated and the onset of arrhythmia and asystole was recorded. The levels of inflammatory cytokines in atria were also measured. Clofibrate significantly postponed the onset of arrhythmia and asystole when compared to control group (P≤0.05 and P≤0.01, resp.). While ouabain significantly increased the atrial beating rate in control group (P≤0.05), same treatment did not show similar effect in clofibrate-treated group (P>0.05). Injection of ouabain significantly increased the atrial and systemic levels of all studied inflammatory cytokines (P≤0.05). Pretreatment with clofibrate could attenuate the ouabain-induced elevation of IL-6 and TNF-α in atria (P≤0.01 and P≤0.05, resp.), as well as ouabain-induced increase in IL-6 in plasma (P≤0.05). Based on our findings, clofibrate may possess antiarrhythmic properties through mitigating the local and systemic inflammatory factors including IL-6 and TNF-α.